2008
DOI: 10.1007/s12024-008-9035-y
|View full text |Cite
|
Sign up to set email alerts
|

Sudden unexpected death in a toddler with Williams syndrome

Abstract: We report a toddler with Williams syndrome (WS) complicated by congenital heart disease and a seizure-like episode who died suddenly several hours after uneventful cardiac catheterization. The cardiovascular anomalies and their association with sudden death as well as the clinical neurological and neuropathologic abnormalities identified in WS are delineated and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…Histiocytoid cardiomyopathy was diagnosed in one case (Case 14) at autopsy by microscopic examination. We previously reported the case of coronary artery stenosis and sudden death in the child with Williams syndrome (Case 12) whose diagnosis was confirmed by a fluorescent in situ hybridization (FISH) study prior to death that showed a heterozygous deletion of band 7q11.23 [ 13 ]. Specific testing during the child’s life was sought based upon the clinical findings suggestive of Williams syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…Histiocytoid cardiomyopathy was diagnosed in one case (Case 14) at autopsy by microscopic examination. We previously reported the case of coronary artery stenosis and sudden death in the child with Williams syndrome (Case 12) whose diagnosis was confirmed by a fluorescent in situ hybridization (FISH) study prior to death that showed a heterozygous deletion of band 7q11.23 [ 13 ]. Specific testing during the child’s life was sought based upon the clinical findings suggestive of Williams syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…In our patient, the risk of catheterization-associated mortality due to intraprocedural fatal arrhythmias and/or cardiac arrest was esteemed too high, also considering poor patient compliance which would have needed deep sedation to accomplish the procedure (Krous et al 2008 ; Bennett et al 2005 ). For such reason, a non-invasive imaging technique was chosen to assess coronary tree anatomy, avoiding sedation or anesthesia.…”
Section: Discussionmentioning
confidence: 88%
“…Thus the occurrence of these two rare conditions in our patient is most likely fortuitous. It is interesting however that patients with Williams carry an increased risk for sudden death which is estimated to be 25 to 100-fold higher than aged matched individuals [ 5 7 ]. The causative factors are thought to be related to the associated cardiac abnormalities, namely, the aortic and pulmonary stenosis as well as to myocardial ischemia secondary to coronary insufficiency.…”
Section: Discussionmentioning
confidence: 99%